2018
DOI: 10.3892/mmr.2018.9583
|View full text |Cite
|
Sign up to set email alerts
|

Two novel pathogenic variants of L1CAM gene in two fetuses with isolated X‑linked hydrocephaly: A case report

Abstract: Hydrocephalus due to aqueductal stenosis (HSAS; Online Mendelian Inheritance in Man #307000) is a rare X-linked, recessively-inherited disease characterized by severe hydrocephaly and occasionally adducted thumbs, in addition to intellectual disability and spasticity in surviving individuals. The present study described two fetuses with severely enlarged ventricles of the brain. The clinical diagnosis of HSAS was made on the basis of family history and sonographic findings. Molecular testing of the L1 cell adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Novel L1CAM mutations included the p.Trp460Cys and p.Trp635Arg deleterious missense mutations, mapping to the fifth (of 6) immunoglobulin-like domain and the first (of 5) extracellular fibronectin domain, respectively; 2 splice site mutations, c.1828 + 1G>A (localizing to intron 15) and c.1546 + 1G>T (located in intron 13) were associated with loss-of-function translation frameshifts; and the stop-gain mutation p.Glu304X. The previously reported deleterious missense mutation p.Val788Phe (localizing to the second fibronectin domain), and the known splice site mutation c.806 + 1G>C (positioned in intron 8), were also identified (Figure). All 6 patients for whom clinical information was available had neurodevelopmental delays.…”
Section: Resultsmentioning
confidence: 99%
“…Novel L1CAM mutations included the p.Trp460Cys and p.Trp635Arg deleterious missense mutations, mapping to the fifth (of 6) immunoglobulin-like domain and the first (of 5) extracellular fibronectin domain, respectively; 2 splice site mutations, c.1828 + 1G>A (localizing to intron 15) and c.1546 + 1G>T (located in intron 13) were associated with loss-of-function translation frameshifts; and the stop-gain mutation p.Glu304X. The previously reported deleterious missense mutation p.Val788Phe (localizing to the second fibronectin domain), and the known splice site mutation c.806 + 1G>C (positioned in intron 8), were also identified (Figure). All 6 patients for whom clinical information was available had neurodevelopmental delays.…”
Section: Resultsmentioning
confidence: 99%
“…Of particular interest, our literature review indicated that among the known genes for AR-HSPs, the most reported CNVs in SPG11 and SPG7 have been mainly linked to the HSP phenotype. Also, CNVs in PLP1 are not an important cause of X-linked SPG2, but CNVs in L1CAM play a crucial role in the development of SPG1 [Kutsche et al, 2002;Xie et al, 2018]. Despite all these informative findings, the exact proportion of HSP cases caused by CNVs and the extent to which these CNVs implicate HSP pathophysiology are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Table S1). SPG1/L1CAM (OMIM # 303350) In SPG1 patients, the two most prevalent types of reported L1CAM variants have been missense and rearrangements [Kutsche et al, 2002;Xie et al, 2018]. The compact gene structure and the low density of repeats in the genomic L1CAM DNA sequence predispose this gene to illegitimate recombination and consequent rearrangements including loss of the complete gene [Kutsche et al, 2002].…”
Section: Clinical Findings Of the Proband Cnv100-iii5mentioning
confidence: 99%
“…[18][19][20] Mutations located in the L1 extracellular regions generally correlate with a more severe phenotype than mutations in the cytoplasmic tail (http://www.l1cam mutat ionda tabase.info/). [21][22][23][24][25] So far, high resolution structural information on fulllength L1 or fragments containing two or more domains of L1's extracellular part has not been obtained. Structural information has mainly been inferred by comparison with other, homologous proteins and from studies mapping functional domains or binding sites within L1 or related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations located in the L1 extracellular regions generally correlate with a more severe phenotype than mutations in the cytoplasmic tail (http://www.l1cammutationdatabase.info/). 21–25 …”
Section: Introductionmentioning
confidence: 99%